2017
DOI: 10.12707/riv17030
|View full text |Cite
|
Sign up to set email alerts
|

School-based interventions for teen dating violence prevention: integrative literature review

Abstract: Intervenções na escola para prevenção da violência nas relações de intimidade entre adolescentes: revisão integrativa da literatura Intervenciones en la escuela para prevenir la violencia en las relaciones íntimas entre adolescentes: revisión integradora de la literatura Diene Monique Carlos*; Ana Beatriz Campeiz**; Jorge Luiz da Silva***; Maria Isabel Domingues Fernandes****; Maria Neto da Cruz Leitão*****; Marta Angelica Iossi Silva******; Maria das Graças Carvalho Ferriani******* Abstract Background: Intima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
1
8
0
6
Order By: Relevance
“…The violence suffered by the adolescents showed association between 12 and 14 years old. The literature corroborates such findings regarding the various types of violence to which adolescents are exposed and warns that these adolescents may live and mean violence in different ways 27 , 32 . Therefore, it suggests the development of instruments that identify and allow more targeted interventions for these age groups.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The violence suffered by the adolescents showed association between 12 and 14 years old. The literature corroborates such findings regarding the various types of violence to which adolescents are exposed and warns that these adolescents may live and mean violence in different ways 27 , 32 . Therefore, it suggests the development of instruments that identify and allow more targeted interventions for these age groups.…”
Section: Discussionsupporting
confidence: 64%
“…Such attitudes of students who witness violence may be motivated by the desire to improve their peer status, as aggressors become popular, or out of fear, in an attitude of self-protection. The literature has pointed out the importance of looking at the spectators of violence among adolescents, who have been neglected by research and interventions; a climate of peace culture can act as a significant protective factor for violence among adolescents 27 - 29 .…”
Section: Discussionmentioning
confidence: 99%
“…27 The health care model, in the face of situations of violence and bullying at school, needs health professionals who broaden their knowledge, taking on new theories and practices capable of responding to the challenge and technical and ethical commitment of guaranteeing equity, protection and improved quality of life in childhood and adolescence, both within health centers and within the school setting. 28 Our study does not represent the behavior of adolescents outside school. This is a limitation which should be explored in future Health research.…”
Section: Discussionmentioning
confidence: 98%
“…This reality can be evidenced in a study undertaken by Carlos et al (47) , which identified that interventions related to affective and sexual relationships carried out in the school environment are usually centered on training aimed at reducing behaviors characterized as risk among adolescents.…”
Section: Discussionmentioning
confidence: 99%